EFEKTIVITAS DISTRIBUSI ZAKAT UNTUK BEASISWA PENA BANGSA DI YDSF SURABAYA - Dini Amelia Rusyadi; Nadhatus Dwi Ayu Rinjanik; Uswatun Hasanah; Yonan Anggianto; Lian Fuad (Jurnal Manajemen, Ekonomi dan Akutansi (JUMEA), 2025)
This study aims to determine the effectiveness of the scholarship funds implemented by the YDSF and the success of the distribution of scholarships to students and students, so that it can be known whether the acquisition of scholes received by the recipients of such scholes has a significant impact. If the YDSF wants to have an enormous impact on the beneficiaries, then the success of the “Pena Bangsa” scholarship program is even greater. The scholarship is used as a form of granting education funds given to students or students as an aid to the cost of education. The research method used is a qualitative method, i.e. data collected scientifically that is then analyzed and described to produce accurate data. The results of the research of the “Pena Bangsa” scholarship program are quite effective, it is demonstrated in the selection phase of the recipients of scholarships, the use of the budget, the benefits perceived by the beneficiaries, and the role of the YDSF in providing training to the receivers of scholes. Therefore, the Penna Bangsa scholarship program has had a positive impact on the recipients of Pena Bangsa scholes, both for orphaned and dhuafa students in Surabaya, where the students receive school fees, school equipment, and the provision of construction facilities.